If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -5)(x + 5) = 22 Reorder the terms: 2(-5 + x)(x + 5) = 22 Reorder the terms: 2(-5 + x)(5 + x) = 22 Multiply (-5 + x) * (5 + x) 2(-5(5 + x) + x(5 + x)) = 22 2((5 * -5 + x * -5) + x(5 + x)) = 22 2((-25 + -5x) + x(5 + x)) = 22 2(-25 + -5x + (5 * x + x * x)) = 22 2(-25 + -5x + (5x + x2)) = 22 Combine like terms: -5x + 5x = 0 2(-25 + 0 + x2) = 22 2(-25 + x2) = 22 (-25 * 2 + x2 * 2) = 22 (-50 + 2x2) = 22 Solving -50 + 2x2 = 22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '50' to each side of the equation. -50 + 50 + 2x2 = 22 + 50 Combine like terms: -50 + 50 = 0 0 + 2x2 = 22 + 50 2x2 = 22 + 50 Combine like terms: 22 + 50 = 72 2x2 = 72 Divide each side by '2'. x2 = 36 Simplifying x2 = 36 Take the square root of each side: x = {-6, 6}
| 7x+7x=45 | | X+(X*.08)=40.34 | | 112=8w | | 9p(p-3)=0 | | 180-(12x-36)-(16x-24)-88= | | 2+4x=-78 | | x(3x-4)=180 | | X+(X*.1)=40.85 | | 3x+84=15 | | 3/8n=5/6 | | 2(7s+3)-8s=2(3s+4)-12 | | 3x+13+25=2+7x | | 56-6=8 | | 3x-2/2x+1=-2 | | -9(2w-9)=0 | | K^2+5k+8=2 | | 50y=200 | | 18x-4x=9-3x | | 4(4-a)-2(a-4)=-10a-2a | | 4x-(30-x)+25=80 | | 15+4x+60=11x+12 | | 30+you=7 | | 2*(24/2y)*y=48 | | 5u(8u-1)=0 | | 4y=14-2x | | -1=-4+b | | (x^69-i^69)(x^69+i^69)=0 | | dy/dx=1/(2x-y^2) | | 7(x+2)=2x+57 | | 108=4z | | y=1/(2x-y^2) | | 0.5=1-e^-((t-1)/10) |